Analysis of Passenger Satisfaction Levels Using the K-Means Cluster and Hierarchial Cluster Methods in Purabaya Sidoarjo Type A Terminal Services - Zahra Khania Putri; Akmal Suryadi (Yayasan Kita Menulis, 2025)
Purabaya Type A Terminal is one of the terminals that provides public transportation facilities in the form of bus transportation ranging from city buses, intra-provincial intercity buses, and inter-city inter-provincial buses. This study aims to analyze the level of passenger satisfaction with the service at the terminal and group each variable into a homogeneous group. The research methods used are the K-means Cluster and Hierarchial Cluster methods. The data from the questionnaire will be grouped into several groups that have relatively homogeneous properties using the help of SPSS software. From the results of the study, the output of Non-Hierarchial clusters was obtained in the form of Initial Cluster Centers, Iteration History, Final Cluster Centers, ANOVA, and Number of Cased In Each Cluster. Meanwhile, the output of the Hierarchial cluster is in the form of Case Processing Summary and Dendogram Using Average Linkage. Through analysis using the cluster method, all variables were obtained including in cluster 1 and none were included in cluster 2, the iterations carried out were 2 times and the valid data value was 100 data with a missing value of 0.